2002
DOI: 10.1051/0004-6361:20011516
|View full text |Cite
|
Sign up to set email alerts
|

ISO spectroscopy of compact HII regions in the Galaxy

Abstract: Abstract. Infrared spectra between 2.3 and 196 µm were taken towards a sample of 45 compact H ii regions using the two spectrometers (SWS and LWS) on board ISO. The primary goal is to determine the distribution of element abundances in the Galaxy, although there are also many other uses of this database. The spectra contain a wealth of information on the ionized gas and the associated photodissociation regions through the atomic fine-structure lines and on the dust properties via the dust emission bands and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
160
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(170 citation statements)
references
References 52 publications
(55 reference statements)
9
160
1
Order By: Relevance
“…Early estimates by Humphreys (1978) gave the distance to the Cassiopeia OB2 star-forming region, of which IRAS 23133+6050 is part, at 2.63 kpc. Peeters et al (2002) found a distance of 5.5 kpc using kinematical methods and ISO-SWS spectroscopy, which agrees with an earlier calculation by Fich & Blitz (1984) who found d = 5.2 ±0.9 kpc. However other authors, for example Lebrón et al (2001), adopt a smaller value of 3.1 kpc, closer to initial estimates, based on spectrophotmetric observations of associated stars as derived by Brand & Blitz (1993).…”
Section: Iras 23133+6050supporting
confidence: 90%
“…Early estimates by Humphreys (1978) gave the distance to the Cassiopeia OB2 star-forming region, of which IRAS 23133+6050 is part, at 2.63 kpc. Peeters et al (2002) found a distance of 5.5 kpc using kinematical methods and ISO-SWS spectroscopy, which agrees with an earlier calculation by Fich & Blitz (1984) who found d = 5.2 ±0.9 kpc. However other authors, for example Lebrón et al (2001), adopt a smaller value of 3.1 kpc, closer to initial estimates, based on spectrophotmetric observations of associated stars as derived by Brand & Blitz (1993).…”
Section: Iras 23133+6050supporting
confidence: 90%
“…Spectroscopy of H ii regions (Roelfsema et al 1998;Peeters et al 2002) shows that no strong nebular emission lines are present in the 24 μm band; the emission is mostly from the continuum. This emission can only be attributed to dust.…”
Section: The Extended Dust Emission At 24 μMmentioning
confidence: 99%
“…and (8 ± 1) × 10 −20 W cm −2 , respectively for the [Ar ], [S ] and [Ne ] lines (Verma et al 2003; see also Table 1) where we have adopted as uncertainties the typical ISO/SWS 1σ absolute flux accuracy (Peeters et al 2002). Line ratios between the ISO/SWS and TIMMI2 fluxes are 1.3 ± 0.3, 1.9 ± 0.1 and 5.7 ± 2.0.…”
Section: Line Fluxes Observed At Different Spatial Resolutionsmentioning
confidence: 99%